Sosialisasi Orang Tua dan Anak dalam Pemutusan Tangan Anak-anak dari Rantai Pasok Pengelolaan Limbah Sampah - Lutfi Alhazami (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The garbage supply chain is an important thing to manage so that waste does not pollute the environment. Garbage needs to be placed in final disposal sites that have been determined by the government, one of which is TPA Rawa Kucing Tangerang. Rawa Kucing TPA in Neglasari District is a waste disposal area for both organic and non-organic waste in Neglasari, Tangerang. This has made many local residents participate in the management and regulation of waste in Tangerang and in the end many residents work as scavengers. But not only parents but also children are involved in picking up trash. This condition is against the International Labor Organization (ILO) to keep children away from adult work. One of the efforts to realize keeping children away from the waste supply chain at the Rawa Kucing TPA is by holding outreach to parents and children and opening free educational activity facilities as a substitute for the scavenger profession for children. This activity gives awareness to parents not to involve children in the waste supply chain and to focus children more on achieving education.